Mass Sensors Based on Capacitive and Piezoelectric Micromachined Ultrasonic Transducers—CMUT and PMUT - Haleh Nazemi; Jenitha Antony Balasingam; Siddharth Swaminathan; Kenson Ambrose; Muhammad Umair Nathani; Tara Ahmadi; Yameema Babu Lopez; Arezoo Emadi (Sensors, 2020)
Microelectromechanical system (MEMS)-based mass sensors are proposed as potential candidates for highly sensitive chemical and gas detection applications owing to their miniaturized structure, low power consumption, and ease of integration with readout circuits. This paper presents a new approach in developing micromachined mass sensors based on capacitive and piezoelectric transducer configurations for use in low concentration level gas detection in a complex environment. These micromachined sensors operate based on a shift in their center resonant frequencies. This shift is caused by a change in the sensor’s effective mass when exposed to the target gas molecules, which is then correlated to the gas concentration level. In this work, capacitive and piezoelectric-based micromachined sensors are investigated and their principle of operation, device structures and configurations, critical design parameters and their candidate fabrication techniques are discussed in detail.